PSYCHOLOGICAL FACTORS OF POSITIVE IMAGE DEVELOPMENT OF YOUNG TEACHER OF THE PEDAGOGICAL INSTITUTE - Байда, С. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The research results of psychological factors which form the positive image of young teacher of pedagogical institutes are highlighted in the article. The image of teachers is interpreted as the purposefully formed, which determines interactive description of external and internal side of personality of teacher that influences on efficiency of his professional activity. Such basic psychological factors of its successful development are distinguished: attractive appearance, effective use of verbal and unverbal means of intercourse, internal accordance of "I'm" character to the selected profession. Key words: psychological factors, development, positive image, young teacher, pedagogical institution.